130 years of heavy metal pollution archived in the shell of the intertidal dog whelk, Nucella lapillus (Gastropoda, Muricidae). (December 2022) - Mayk, Dennis; Harper, Elizabeth M.; Fietzke, Jan; Backeljau, Thierry; Peck, Lloyd S.
Abstract: Heavy metals in coastal waters are a great environmental concern in the North Sea since the middle of the 20th century. Regulatory efforts have led to a significant reduction in atmospheric and water-transported heavy metals. Still, high concentrations of these in sediments remain a risk for ecosystems, requiring close monitoring. Here, we investigated the applicability of Nucella lapillus museum collections as a tool for targeted tracking of chronic anthropogenic heavy metal pollution. We analysed the concentration ratios of the common heavy metals Cu, Cd, Pb, and Zn in relation to Ca in N. lapillus shells collected from the Dutch and Belgian intertidal zone over the last 130 years. We found that shell Cu/Ca and Zn/Ca concentration ratios remained remarkably constant, whereas Pb/Ca concentration trends were closely aligned with emissions of leaded petrol in Europe. Our results suggest that N. lapillus provides a suitable Pb pollution archive of the intertidal zone. Highlights: European legislation resulted in significant reduction in shell-bound lead. Intertidal muricid represents a suitable archive for lead pollution. Shell-bound copper and zinc not related to environmental concentrations.